Aspects of learning - O'Connell, Brian (London : Routledge, 2012)
The time has passed when learning was identified purely as a process involving the ability to store and recall knowledge and facts, and the competence to produce them when required. These abilities still seriously concern the potential teacher and this book duly examines them, but the 'whys' and the 'hows' of learning and teaching are now considered as important as the implanting of facts for regurgitation at exam time.Some children learn more quickly than others, some can remember facts more easily, and a teacher must ask several fundamental questions in order to understand the factors at wor
Includes bibliographical references and index.
Keywords: Learning, Psychology of; Educational psychology; EDUCATION -- Educational Psychology